Essays on the use of nightligts to measure economics performance - Velilla Gómez, Raúl Alfonso (2022)
This thesis consists of three essays on the use of nightligts to measure economic activity in two developing countries. In the first essay, we analyze the effect of the Action Plan for the Prevention and Control of Deforestation in the Legal Amazon (PPCDAm) on economic activity in Brazil. The PPCDAm was an initiative of the Brazilian government that aimed to reduce the high rates of deforestation that the country was experiencing at the beginning of the 2000s. Although the program was directed directly to an environmental problem, it could indirectly have effects on economic activity since part of the productive activities in the Amazon are linked to deforestation. To do that, we use two empirical approaches: first, we compare the economic activity (measured as night light density) of municipalities inside and outside Brazilian Amazon before and after PPCDAm implementation in a difference in difference approach. Our results reveal that municipalities inside Amazon experiment a descrease in night lights intensity after 4 year of implementation of PPCDAm. Second, we exploit the geographical limits between Brazil and the other neighboring countries with which Brazil shares part of the Legal Amazon in order to estimate the effect of PPCDAm on economic activity. Specifically, we used regression discontinuity approach, which permits us to compare the economic activity, measured as the intensity of lights at night, on the border of the Brazilian Amazon Forest with its close neighbors. We estimated a regression discontinuity models year by year in order to understand the evolution of the economic activity before and after PPCDAm implementation. The results reveal that before the PPCDAm implementation the night light intensity in the Brazilian border was higher than its relative neighbors, however after the policy its neighbors experience high intensity during the three first years. In the second essay, we take advantage of a natural experiment - the creation of new Brazil capital (Brasília) in the decade of the 60’s – and the subsequent construction of a new road system to analyze the persistence of public investment in road infrastructure on economic activity. The findings show that microregions located near the highway corridor experiment higher night light intensity relative to microregions faraway. In the last essay, exploiting the international coffee price boom and municipal coffee intensity production, we study how commodities price shocks affect local economic activity in Colombia. Our results indicate that, on average, coffee-producing municipalities experience greater luminosity after the unexpected increase in international coffee prices than non-producing municipalities. Keywords: Nighttime Light. Public Policy. Developing country.